2000
DOI: 10.1007/s00418-004-0711-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the small heat shock proteins ?B-crystallin, MKBP, HSP25, HSP20, and cvHSP in heart and skeletal muscle

Abstract: Seven members of the small heat shock protein (sHSP) family are exceptional with respect to their constitutive high abundance in muscle tissue. It has been suggested that sHSPs displaying chaperone-like properties may stabilize myofibrillar proteins during stress conditions and prevent them from loss of function. In the present study five sHSPs (alphaB-crystallin, MKBP, HSP25, HSP20, and cvHSP) were investigated with respect to similarities and differences of their expression in heart and skeletal muscle under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
161
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(186 citation statements)
references
References 51 publications
17
161
0
8
Order By: Relevance
“…These three HSPs were more abundant in LT than in ST and in young bulls compared to steers. These results are consistent with the study of Golenhofen et al (2004) in rats, showing a higher abundance of HSPs in soleus (slow oxidative) compared to extensor digitorum longus (fast glycolytic) muscle. In cattle, LT contains a lower proportion of fast glycolytic fibres and higher proportion of oxidative fibres (I and IIa) compared with ST .…”
Section: Hspssupporting
confidence: 92%
See 2 more Smart Citations
“…These three HSPs were more abundant in LT than in ST and in young bulls compared to steers. These results are consistent with the study of Golenhofen et al (2004) in rats, showing a higher abundance of HSPs in soleus (slow oxidative) compared to extensor digitorum longus (fast glycolytic) muscle. In cattle, LT contains a lower proportion of fast glycolytic fibres and higher proportion of oxidative fibres (I and IIa) compared with ST .…”
Section: Hspssupporting
confidence: 92%
“…There are very few data in the literature on differences in HSP expression according to the muscle type. Our results in Protein content according to muscle and animal types cattle with those of Golenhofen et al (2004) in rats, show that HSPs form a complex stress-response system in skeletal muscle with some common and some distinct functions between different muscle types. Golenhofen et al (2004), using immunostaining, showed a higher intensity with an antiaB-crystallin antibody in type I fibres compared to II fibres.…”
Section: Hspsmentioning
confidence: 57%
See 1 more Smart Citation
“…HSP27, HSP90, and alphaB-crystallin-related B6 were identified in the nuclear fraction of the gastrocnemius muscle, whereas HSP27, HSP70, HSP90, HSP1 (chaperonin), heat shock protein (HSP) family member 7, and cryab protein were identified in the nuclear fraction of the soleus muscle. The presence of HSP1 in soleus is in agreement with the observed overexpression of this protein shown by Golenhofen and coworkers [32] when comparing soleus with gastrocnemius. The notion of more members of the HSP family confirms the functional properties of the red soleus muscle, and this would make this muscle more susceptible to stress conditions related to HSP as compared with the white portion of the gastrocnemius muscle.…”
Section: Discussionsupporting
confidence: 90%
“…In the heart, cardio myocytes express high levels of specific mem bers of one of the small HSP families, the HSPBs. These include HSPB1 (HSP27), HSPB5 (α crystallin B chain), HSPB6 (HSP20), HSPB7 (cardiovascular HSP), and HSPB8 (HSP22), and are considered to safeguard cardiomyocytes from proteotoxicity by stabilizing the contractile apparatus 38,39 .…”
Section: The Proteostasis Network Componentsmentioning
confidence: 99%